(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This article explores the Communicative Approach in foreign language instruction, focusing on its theoretical background, methodological principles, and practical implementation. By conducting an extensive literature review that includes both international and Uzbek sources, the study examines the development of the Communicative Approach, its influence on language acquisition, and its effectiveness in enhancing learners’ communicative competence.